Effect of the Think Talk Write Cooperative Learning Model Assisted by Poster Media on Students’ Learning Outcomes in Biology Among Grade VIII Students at SMP Negeri 19 Palu - Al Hadar, Nuraziza Z; Astija; Sabran, Moh.; Bustamin; Isnainar; Bialangi, Mursito S. (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to examine the effect of a poster-assisted Think Talk Write cooperative learning model on eighth-grade students’ learning outcomes in biology at SMP Negeri 19 Palu. A quasi-experimental method was employed using a nonequivalent control group design. The study involved two classes selected through purposive sampling: Class VIII A, consisting of 31 students, served as the control group, while Class VIII C, consisting of 28 students, served as the experimental group. Data were collected using a multiple-choice achievement test. The findings showed that the poster-assisted Think Talk Write cooperative learning model had a significant effect on students’ learning outcomes in the topic of the excretory system. The Mann–Whitney U test comparing the posttest scores of the experimental and control groups yielded an Asymp. Sig. (two-tailed) value of 0.001, which was lower than the significance level of 0.05. This result indicated a statistically significant difference between the two groups after the intervention. Furthermore, the experimental group achieved a mean normalized gain of 73% (g = 0.73), which was higher than that of the control group, which achieved 55% (g = 0.55). These findings demonstrate that the poster-assisted Think Talk Write learning model significantly improves students’ biology learning outcomes. Therefore, this model may be considered an effective alternative instructional strategy for enhancing student achievement.